2018
DOI: 10.1016/j.bbadis.2018.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin inhibits hepatic stellate cell activation by targeting the PTEN/AKT pathway

Abstract: Adiponectin inhibits hepatic stellate cell (HSC) activation and subsequent development of liver fibrosis via multiple mechanisms. Phosphatase and tensin homolog deletion 10 (PTEN) plays a crucial role in suppression of HSC activation, but its regulation by adiponectin is not fully understood. Here, we investigated the effect of adiponectin on PTEN in LX-2 cells, a human cell line and examined the underlying molecular mechanisms involved in adiponectin-mediated upregulation of PTEN activity during fibrosis. PTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…There is a growing interest in epigenetic molecular mechanisms for investigations and therapeutic purpose. Aberrant DNMT expressions have been found in liver fibrosis conditions, 21 In conclusion, our study demonstrates that epigenetic silencing of LncRNA ANRIL regulates HSC activation though AMPK pathway is crucial pro-fibrogenic components forming an epigenetic cascade promoting liver fibrosis. This is a novel understanding of the role of DNMT3A and LncRNA ANRIL in HSC proliferation and the mechanism involved.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…There is a growing interest in epigenetic molecular mechanisms for investigations and therapeutic purpose. Aberrant DNMT expressions have been found in liver fibrosis conditions, 21 In conclusion, our study demonstrates that epigenetic silencing of LncRNA ANRIL regulates HSC activation though AMPK pathway is crucial pro-fibrogenic components forming an epigenetic cascade promoting liver fibrosis. This is a novel understanding of the role of DNMT3A and LncRNA ANRIL in HSC proliferation and the mechanism involved.…”
Section: Discussionmentioning
confidence: 55%
“…There is a growing interest in epigenetic molecular mechanisms for investigations and therapeutic purpose. Aberrant DNMT expressions have been found in liver fibrosis conditions, but the information regarding specific DNMT subtype involved in liver fibrosis is not appreciatively established. Accumulating evidence indicates the existence of cross regulation between DNA methylation and LncRNAs in the control of gene expression …”
Section: Discussionmentioning
confidence: 99%
“…Decreased PTEN controlled by miRNAs in the liver is a mechanism of fibrogenesis. PI3K/AKT pathway is believed to regulate liver fibrosis,3233 Its upstream natural inhibitor PTEN exhibits a tumor suppressor role and is dysregulated in liver diseases 1934. PTEN has recently been identified as a target/biomarker for pharmacological therapy of liver fibrosis,35 and approaches to decrease PTEN expression would be promising strategies in liver injury 3436.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that miR-29b could increase PTEN methylation via decreasing DNMT3b expression 15,16 . Next, we determined whether miR-29b was involved in regulating DNMT3b expression.…”
Section: Resultsmentioning
confidence: 99%
“…Adiponectin inhibits hepatic stellate cell activation via regulating PTEN expression. Mechanistically, upregulation of miR-29b induced by adiponectin can suppress DNMT3b transcription, leading to reduced PTEN methylation and ultimately suppressing the PI3K/AKT pathway 15 . HOTAIR, as a long intergenic non-coding RNA, downregulates miR-29b expression, leading to enhanced DNA methylation of PTEN promoter, which induces decreased PTEN expression 16 .…”
Section: Introductionmentioning
confidence: 99%